Persistent disconnect between flow restoration and restoration of river ecosystem functions after the removal of a large dam on the Sélune River - Piscart, Christophe; Dézerald, Olivier; Pellan, Laura; Le Bris, Nathalie; Rodríguez-Pérez, Héctor; Beauverger, Thibaut; Huteau, Dominique; Roussel, Jean-Marc (Frontiers in Environmental Science, 2024)
The removal of the two dams on the Sélune River since 2019 has led to profound changes in the aquatic ecosystem. Lentic habitats bordered by forest had shifted to new conditions (running water and sparsely vegetated riverbanks) therefore shaping organisms' assemblies. We studied how the reestablishment of aquatic lotic habitats in interaction with riparian vegetation could mediate the restoration of important ecological functions in the new river. Six stations located along the river continuum were surveyed for three years after dam removal: two control stations upstream the former reservoir, three restored stations within the former reservoir, and one control station downstream. We monitored physico-chemical characteristics, phytobenthos biomass and the river's benthic metabolism, and assessed the functional composition of macroinvertebrate communities. We compared the recorded variables among upstream, downstream and restored sampling stations. We observed a rapid recolonization by invertebrates, but a still low phytobenthic primary production in restored stations. Such a low primary productivity was also reflected in the functional composition of invertebrate communities. Three years after dam removal, there was still a significant time lag between communities recovery and expected ecosystem functioning restoration. We observed a quick colonization by aquatic running-water invertebrate communities of new lotic reaches, but a slower recovery of important ecological functions rates such as those observed in control stations.